Highlights from the First Annual Spinal Navigation, Emerging Technologies and Systems Integration Meeting - Drazin, Doniel; Grunert, Peter; Hartl, Roger; Polly, David; Meyer, Bernhard; Catchpole, Ken; Laufer, Ilya; Sethi, Rajiv; Perry, Tiffany; Simon, David; Wang, Michael; Fisher, Charles; et al. (Annals of Translational Medicine, 2018)
This paper provides a detailed report of the “First Annual Spinal Navigation, Emerging Technologies and Systems Integration” meeting held December 3, 2016 at the Seattle Science Foundation.